Bauran Pemasaran Bunga Krisan pada Kelompok Usaha Bersama Manik Mekar Nadi di Desa Besakih, Kecamatan Rendang, Kabupaten Karangasem - PERMANA, I MADE RIYAN; SUAMBA, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.1, Januari 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT The Marketing Mix of Chrysanthemum Flower in KUBE Manik Mekar Nadi in Besakih Village, Rendang District, Karangasem Regency The marketing mix is a combination of four variables which constitute the core of the company's marketing system, consisting of product, price, place / distribution and promotion channels. This study aims to determine the marketing mix by KUBE Manik Mekar Nadi, margins obtained each marketing agencies involved, and the constraints faced in marketing their products. Locations were selected by purposive sampling. Types of data collected include qualitative data and quantitative data derived from primary data and secondary data. Data were collected by interview, observation, documentation studies and literature methods. Data was analyzed by descriptive qualitative and quantitative margin analysis.Based on the survey results revealed that KUBE Manik Mekar Nadi offers products with a wide variety of cut flower chrysanthemum color with three product classes, namely class products A, B, and C. KUBE product packaging by binding each of 10 trees that have been cut flowers using a rubber band, then wrapped using white manila paper. Determination of the selling price from the cost of the product, as well as look at the market price. Promotions conducted KUBE through exhibitions, discounts, and participate in seminars agricultural activities. Marketing margin on each successive line of Rp.2500 Tutut, 00 for C product on line (I), Rp.8000, 00 for product A, Rp.7.500, 00 for product B on a channel (II), and Rp .9000,00 for product A, Rp.8000, 00 for product B on line (III). Constraints faced by the KUBE not have private transportation means to distribute the product. Additionally KUBE difficulty in meeting the demand coming regularly. It is recommended to KUBE that have personal transportation to distribute the product, and immediately increase the amount of greenhouse so that the production cycle is not broken / blocked.